Costs and efficacy ofolanzapine and risperidone in schizophrenia - Mapelli, Vittorio (Farmeconomia. Health Economics and Therapeutic Pathways, 2007)
Introduction: schizophrenia is a serious and long lasting psychiatric disease. The new “atypical” antipsychotic drugs, introduced in the 90s, have substantially improved the effectiveness of medical treatments, compared to previous neuroleptic drugs. Nowadays they tend to be used as first choice drugs. The ddd cost of atypicals may differ by 20% and health authorities may have an incentive to deliver the less costly drug, especially if they are generic. However the various drugs show differential effectiveness rates and a rational choice should consider both cost and effectiveness. Objective: the purpose of this analysis is to review the existing evidence on cost-effectiveness studies of olanzapine and risperidone, the two most prescribed drugs in Italy. Six published studies were identified, but attention was focused on two articles that reported consistent and methodologically sound results. Results: most reviewed studies are cost-minimization analyses, since effectiveness indicators show no significant statistical difference between the two drugs, and are inconclusive since the results depend on the evaluation setting. However one observational retrospective study showed a significant severity reduction over 12 months for patients treated with olanzapine (-2.46 on HoNOS scale; p<0.05), compared to a smaller non significant reduction of the risperidone group (-0.57). Despite the higher drug cost, the average total cost per reduced severity score was lower for olanzapine than for risperidone patients (€ 4,554 vs. € 10,897). The only medical and related health care costs for risperidone patients were higher than total costs for olanzapine patients. Another study comparing cohorts of patients with similar starting severity showed a significant severity reduction and global functioning increase over 12 months for olanzapine but no significant increase for risperidone patients (-0.35, p<0.01 on CGI scale; +3.66, p <0.05 on GAF scale, compared respectively to -0.27, p<0.05 and +2.00 n.s.). Again average cost per reduced severity/increased functioning score was higher for risperidone than olanzapine patients (€ 4,568 vs. € 4,170 for CGI and € 2,284 vs. € 1,139 for GAF scales respectively). Conclusion: the use of olanzapine in the treatment of schizophrenia is the most cost-effective alternative for the SSN (Italian National health service), as it minimizes the cost per score of severity reduction or functioning increase. Even if the price of risperidone were to be reduced by 50% (becoming a generic), total 12 months treatment costs would exceed those of olanzapine in its highest ddd (30 mg).